2013
DOI: 10.21273/jashs.138.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Exogenous Spermidine on Nitrogen Metabolism in Tomato Seedlings Exposed to Saline-alkaline Stress

Abstract: We studied the effects of exogenous spermidine (Spd) on plant growth and nitrogen metabolism in two cultivars of tomato (Solanum lycopersicum) that have differential sensitivity to mixed salinity-alkalinity stress: ‘Jinpeng Chaoguan’ (salt-tolerant) and ‘Zhongza No. 9’ (salt-sensitive). Seedling growth of both tomato cultivars was inhibited by salinity-alkalinity stress, but Spd treatment alleviated the growth reduction to some extent, especially in ‘Zhongza No. 9’. Exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Previous studies have shown that drought stress can increase the NH 4 + content in bamboo [51] and tomato [46]. NH 4 + is produced by the NO 3 − assimilation and oxidation of glycine during the photorespiration process under stress conditions, and excessive accumulation of NH 4 + is detrimental to plants, as it can trigger protein extrusion and disturb cytosolic pH [7,52]. GS is responsible for glutamine synthesis in the NH 4 + assimilation process as the entry point of inorganic N into the organic form, and GOGAT is responsible for catalysing the transfer of the amide group of glutamine to 2-oxoglutarate, generating glutamate simultaneously [46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that drought stress can increase the NH 4 + content in bamboo [51] and tomato [46]. NH 4 + is produced by the NO 3 − assimilation and oxidation of glycine during the photorespiration process under stress conditions, and excessive accumulation of NH 4 + is detrimental to plants, as it can trigger protein extrusion and disturb cytosolic pH [7,52]. GS is responsible for glutamine synthesis in the NH 4 + assimilation process as the entry point of inorganic N into the organic form, and GOGAT is responsible for catalysing the transfer of the amide group of glutamine to 2-oxoglutarate, generating glutamate simultaneously [46].…”
Section: Discussionmentioning
confidence: 99%
“…For humans, excessive intake of Cad can cause low blood pressure and heart rate, paralysis of the extremities and potentiation of toxicity of other amines (Moinard et al, 2005). However, analyzed plants were well below the limits of daily intake of these amines, which are essential for the development, growth and stress tolerance in all plants (Kalac & Krausova, 2005;Nishimura et al, 2006;Zhang et al, 2013a). In fact, foods of most concern are meat products, seafood, fermented products and cheeses (Kalac & Krausova, 2005).…”
Section: Analysis Of Free + Conjugated Pas By Gas Chromatographymentioning
confidence: 99%
“…According to Zhang et al (2013a), stress intensity and the levels of polyamines, as well as the specific mechanism of regulation of PAs, are very obscure and controversial. However, the protective role of Spd and Spm against salt stress is well documented in some plants.…”
Section: Analysis Of Free + Conjugated Pas By Gas Chromatographymentioning
confidence: 99%
See 2 more Smart Citations